Neuroekonomi Interdependensi - Hadi, Cholichul (Penerbit Goodwood, 2024)
Purpose: This study aims to examine how sacred values modulate neural representations in interdependent decision-making by comparing brain activation patterns between ultra-Orthodox (with high communal interdependence) and secular Israeli dyads. Research Methodology: An experimental study was conducted with 60 dyads using a modified prisoner’s dilemma paradigm. Decision-making processes were recorded using hyperscanning fMRI. The analyses focused on (1) brain-to-brain synchronization in the dorsomedial prefrontal cortex (dmPFC) and (2) sacred value encoding in the ventral striatum. Results: Findings revealed that Ultra-Orthodox dyads exhibited stronger dmPFC coupling (t = 3.11, p = 0.002), indicating greater cognitive coordination. However, they also showed weaker striatal reward activation when sacrificing for a partner compared to secular couples. This finding suggests a distinct neural trade-off pattern in groups with high interdependence. Conclusions: Sacred-value-based interdependence uniquely shapes brain-to-brain dynamics, implying that culture and religious values modulate the neural representation of cooperation. Limitations: he study is limited to an Israeli sample with a specific religious context; therefore, generalization to other cultures requires further research. Contribution: This research advances the cultural neuroscience literature by showing that interdependence is not only social but also embedded in neural mechanisms. These findings are relevant for developing conflict resolution strategies in polarized societies.